MODEL MANAJEMEN STRATEJIK PENDIDIKAN DAN PELATIHAN DALAM PENGEMBANGAN KUALITAS SUMBER DAYA MANUSIA : Suatu Studi di Divisi Pendidikan dan Pelatihan PT.Telekomunikasi Indonesia - Dody Hermana, - (2006)
Training and education is one of the efforts made to improve human resources work performance by PT. Telkom of which the aim is to provide training and education for participants or trainees to improve their effectiveness, efficiency, and productivity for the company. The improvement of human resources quality is geard toward the enhancement of the functions in operating educational administration.The research was focused on five main problems including (1) Training and Education programs which were applied based on vision, mission, and strategy applied by the company; (2) Training needs assessment for the need in improving human resources quality appropriate with the demand of organizational formation and job description; (3) Training and Education procedures in training and education program in PT.Telkom (4) Factors which support and hinder the process of training and education; (5) A program model of training and education strategic management which should be effective and efficient worth developing in PT.Telkom.This research was conducted in PT. Telkom by using qualitative approach, through documentation study, obsei-vation, literature, and interviews. The research objects are the organizers, teachers, trainees, and the alumni of the training and education program.The results of the research conclude that (I) PT.Telkom as one of the organizers in Telecommunication Service cannot be separated by global telecommunication development. (2) The improvement of human resources based on competency will give optimal results which purpose and target have been determined. (3) As an effort to win competition, it needs quality improvement continuously endeavoured in line with the needs changes, will and hope, and consumers' demand. (4) Vision which says that human resources need to face the future of more competitive enterprise in the globalization era and is qualified enough to maintain human resources productive.Recommendation; (I) It needs to be realized that improving human resources to be able to compete with the same kind of companies requires high commitment of management in performing the company's policy. (2) To be able to compete and win by improving the quality, it is suggested that the company use Total Quality Management. (3) This approach is performed to maximize organizational competitive power through continuous improvement in its production, services, human beings, processes, and environments. (4) To make training and education program become more effective, it is suggested that the company conduct Strategic Learning Approach". (5) To consider efficiency, effectiveness, and productivity, it is suggested that the process of learning and teaching be conducted by long distance learning by using multi media facilities.